A Fast, Visual, and Instrument-free Platform Involving Rapid DNA Extraction, Chemical Heating, and Recombinase Aided Amplification for On-Site Nucleic Acid Detection - Wang, Xiao Fu; Chen, Wen Qiang; Guo, Jian Li; Peng, Cheng; Chen, Xiao Yun; Xu, Xiao Li; Wei, Wei; Yang, Lei; Ca, Jian; Xu, Jun Feng (Frontiers in Bioengineering and Biotechnology, 2021)
The nucleic acid-based technique has been widely utilized in many fields including for on-site detection. However, traditional molecular detection techniques encounter limitations like relying on instruments, time consuming or complex operation, and cannot meet the demands of on-site testing. In this study, a rapid DNA extraction method (RDEM), recombinase aided amplification (RAA), and chemical heating packet (CHP) are integrated and termed as RRC platform for on-site detection of nucleic acid. For demonstration purposes, SHZD32-1 (a new transgenic soybean line from China) was detected using the novel platform to demonstrate its feasibility and capability for on-site detection. Using the RDEM, high-quality DNA appropriate for molecular detection was quickly extracted in 3-5 min. The heat energy generated by CHP was met the temperature requirements of RAA. Using the RRC platform, the whole detection process can be accomplished within only 30 min, and the results can be visually detected with glasses under blue light. No special or expensive instrument was needed for the detection process. This study provides a novel approach for on-site detection of nucleic acids besides providing valuable insight on related future research.